Instructional Communication in International High School in DKI Jakarta: A Case Study - RATIH, Dina S.V.; CANGARA, Hafied; SANTOSA, Nandang M. (International Journal of Environmental, Sustainability, and Social Science, 2023)
Instructional communication is an important element in educational communication between teachers and students. The high school international school environment is different from the national school. This study aims to find out the influence and results of analysis on international school standards and teacher competence in high schools located in DKI Jakarta on instructional communication and communication behaviour. The methodology used is a mixed sequential explanatory method, conducting a survey of high school level students at an international school in DKI Jakarta and processed through semi-structural interviews and literature. The results shown that international school standards directly influence communication behaviour but not directly affect instructional communication. While teacher competence directly influences instructional communication, not directly affect communication behaviour. However, instructional communication as an intervening variable increases influence on international school standards and teacher competence on communication behaviour. Hence, the environment and the teacher's competence influence how the teacher teaches and acts as a model through verbal and nonverbal instructional communication. However, cultural and experiential also influence how Indonesian and foreign teachers apply instructional communication and react to students. The reactions of the two communities are sometimes different and have an impact on the profile of students who study abroad.